Education on Financial Management & Access to Fintech Peer to Peer Lending Financing in the Context of Improving Financial Literacy for the Independent Independent Community (SBM) as Creative Economy Business Actors in Jambi Province - Sartika, Dewi; Fitriasuri, Fitriasuri; Noviardy, Andrian; Fitriyani, Rosha; Yama Lestari, Riski (PT FORMOSA CENDEKIA GLOBAL, 2025)
This national community service aims to increase financial literacy in financial management and access to financing for MSME actors of the Independent Friends Community (SBM) in Jambi Province. This activity involves training and counseling using lectures, simulations, and direct guidance methods. Participants were given material on financial records, business feasibility analysis, and the use of peer-to-peer lending fintech technology. The implementation was carried out in a structured manner, starting from observation and interviews, followed by intensive training for several days. The results showed an increase in participants' awareness of the importance of financial management and access to financing, as well as enthusiasm in technology adoption. The implication is better business development opportunities and a positive contribution to local economic growth.